Early Holocene secondary burials in the Pampas of Argentina - Scabuzzo, Clara (2007)
In this paper we analyze and discuss two new secondary burials from the Arroyo Seco 2 archaeological site and present new 14C evidence that places them in the early Holocene. They are the earliest evidence of this kind of inhumation in the Pampas and Patagonia.